2006
DOI: 10.1007/s10620-006-9177-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oxidative Stress and Leucocyte Activation in Neoplastic Tissues of the Colon

Abstract: Excess of intracellular reactive oxygen species results in an environment that may modulate gene expression, or damage cellular molecules. These events are assumed to contribute to the process of carcinogenesis. In the present study, we measured the extent of lipid peroxidation and antioxidative status in colonic tumors and normal colonic mucosa obtained from 25 patients with colorectal carcinoma. Levels of lipid peroxides (PD) and of thiobarbituric acid reactive substances (TBARS) were significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 27 publications
5
61
0
8
Order By: Relevance
“…The level of GSH and GSH dependent enzymes were raised along with the increase in the apoptosis. Increase in the activities of SOD and CAT in the carcinogen treated animals have also been reported by other workers [52,53]. An increased expression of GSH, GPx and GST in the neoplastic cell confers a selective growth advantage against onslaught of oxidative stress and allows these cells to propagate and proliferate [54].…”
Section: Discussionsupporting
confidence: 61%
“…The level of GSH and GSH dependent enzymes were raised along with the increase in the apoptosis. Increase in the activities of SOD and CAT in the carcinogen treated animals have also been reported by other workers [52,53]. An increased expression of GSH, GPx and GST in the neoplastic cell confers a selective growth advantage against onslaught of oxidative stress and allows these cells to propagate and proliferate [54].…”
Section: Discussionsupporting
confidence: 61%
“…The raised TBARS indicates the weak antioxidant defense system against raised OS. There were numerous reports indicating raised OS in cancer patients due to alcohol consumption (Terry et al, 2001;Poschl and Seitz, 2004;Rainis et al, 2007;Ha et al, 2010;Manjunath et al, 2010). Not only the commercial alcohol but also the combination of alcohol and commercial alcohol consumption plays an important role in increased OS and further in cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Since the intestinal mucosa is constantly confronting with diet and bacterial-derived oxidants and carcinogens, an unrestrained production of free radicals, redox imbalance, and DNA damage occurs, finally leads to an altered intestinal metabolic homeostasis with cancer as an endpoint [133]. The human colorectal tumors have increased levels of nitric oxide (NO) [132], 8-oxodG in DNA [133], and lipid peroxides [134]. Suzuki et al 2004 [135] have reported increased serum levels of oxidized low density lipoprotein in patients with CRC compared to healthy individuals.…”
Section: Colorectal Cancermentioning
confidence: 99%